Load Balancing on TJSB Transformer Distribution using Two-Points Time Method - Jimmy Trio Putra; Mohammad Arsyad (Universitas Ahmad Dahlan, 2018)
The load unbalances is caused by single phase loads on low voltage network consumers. In the design of three-phase transformer loads are generally designed in a balanced way, but in reality that occurs, the distribution of transformer load in the network is not balanced. This unbalance can lead the current to flow in a neutral conductor if not observed accordingly. The flowing current in the transformer's neutral conductor can cause losses. This paper discusses load balancing using the two-point time method as a recommendation for moving the consumer's load from one phase to another phase. This study used real data by performing direct measurements on the loading of TJSB transformer Pabuaran feeder of PT (PLN) Persero Sukabumi Region both before and after the load balancing. The results obtained after the load balancing include the percentage of unbalance during the day that is 5% which was previously 16% and at night become 5.6% from 25.6%. The initial neutral current was 44 A and decreased to be 16 A during the day, while at night decreased from 68 A to 24 A. Power losses due to neutral currents flowing in the neutral conductor obtained at noon i.e. 0.19 kW from previously 1.32 kW and at night 0.39 kW from the previous 2.3 kW.